Origin and behaviour of emphysematous bullae. - Morgan, M D (1989)
Giant emphysematous bullae are believed to produce symptoms of pulmonary compression and collapse by containing gas under pressure that has been generated through valvular feeding airways. To examine this hypothesis, we have measured oxygen and carbon dioxide tensions (PO2, PCO2) in four patients and pressure within the bullae in three patients immediately before surgery. During spontaneous tidal respiration PO2 in the bulla was higher than arterial PO2 but did not rise as fast during the breathing of oxygen. The intra-bulla pressure during inspiration was negative (-5.5 to -19 cm H2O) and similar to pleural pressure in phase and degree. During intermittent positive pressure ventilation in two patients airway pressures were transmitted to the bulla with the development of a positive end expiratory pressure within the bulla. Histological examination of the walls of the bullae in the four patients and adjacent lung tissue in an additional patient failed to identify any valvular mechanism. The available information suggests that bullae develop after retraction and collapse of surrounding lung away from a region of weakness.